Path to posttraumatic growth: The role of centrality of event, deliberate and intrusive rumination, and self blame in women victims and survivors of intimate partner violence - Bakaitytė, Aistė; Puente-Martínez, Alicia; Ubilos-Landa, Silvia; Žukauskienė, Rita (Frontiers in Psychology, 2022)
Increased interest in positive changes in the aftermath of traumatic events led researchers to examine assumptions about the process of posttraumatic growth (PTG). However, existing studies often use samples from mixed trauma survivors and investigate separate factors and their associations with growth. Therefore, the purpose of the current study was to examine the path from centrality of event to PTG involving intrusive and deliberate rumination and self-blame as a coping strategy in women survivors of intimate partner violence (IPV). The study sample consisted of 200 women with a history of IPV (ages 18 - 69, M = 44.79, SD = 12.94). Results of the path analysis indicated that higher centrality of event was related to higher levels of intrusive rumination which was positively related to self-blame and deliberate rumination eventually leading to PTG. Indirect effects from centrality of event to PTG through intrusive and deliberate rumination, and from intrusive to deliberate rumination through self-blame were examined. This study gave support to some theoretical assumptions of the process of PTG and pointed out problematic areas of investigation of coping strategies in this process.